1-D two-phase flow analysis for interlocking double layer counter flow mini-channel heat sink. (June 2019) - Lim, Kihoon; Lee, Jaeseon
Highlights: An interlocking double layer counter flow channel heat sink for IGBT is proposed. The heat sink performance predicted by the 1-D flow boiling model for counter flow. The model analysis is performed by iterative operations by genetic algorithm. The benefits of counter flow are uniform surface temperature and low thermal resistance. Abstract: Mini and micro-channel heat sinks with two-phase flow boiling are considered as one of the promising cooling methods due to their ability to efficiently manage high heat flux heat dissipation. However, it is characterized by a significant decrease in the heat transfer coefficient of the liquid deficient portion where the quality of flow is increased by the boiling in the channel. The heat transfer coefficient at which the wall dry-out occurs sharply decreases, which can cause a large temperature gradient in the direction of flow. Such a dry-out condition may correspond to the critical heat flux state, and a drastic decrease in cooling performance is inevitable. To alleviate the temperature gradient increase and to improve the cooling performance, the two-phase counter flow mini-channel heat sink with interlocking double layer structure has been proposed. The proposed mini-channel heat sink was designed based on the commercial IGBT module size and numerically analyzed by applying 1-D two-phase flow in each counter flow direction. Two-phase boiling heat transfer correlation and momentum equation were solved to calculate the pressure drop and analyze the cooling performance benefits of proposed counter flow heat sink. The applied analysis method was extended to the single-phase counter flow situation and the results were compared with two-phase flow case. From the results of the analysis, it was confirmed that the counter flow heat sink can obtain a more uniform temperature distribution than the conventional unidirectional heat sink. The non-uniformity of the temperature distribution due to the uneven flow rate of the parallel channels can be improved by applying the counter flow configuration.